2015
DOI: 10.3765/salt.v0i0.2898
|View full text |Cite
|
Sign up to set email alerts
|

A New Semantics for Number

Abstract: Research on the semantics of number has been strongly influenced by the distri bution of overt number morphology in English. As is well know, number can be expressed on nouns and on verbs in English. In example (1), overt plural morphol ogy is present in both places.(1)The books- [PL] were-[pL] lying on the table.All research on plurality has assumed the the [pI]-feature on the noun is interpreted in some way. Bennett (1974) was the first to propose a semantics of number along these lines, and this assumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 3 publications
(5 reference statements)
3
41
0
Order By: Relevance
“…Finding sensitivity to both singular and plural agreement errors, we concluded that number in the native baseline is a multi-valued feature (both singular and plural are specified feature values; cf. Sauerland 2003;Scontras 2013a;. Finding sensitivity only to agreement errors involving feminine adjectives, we concluded that gender is single-valued (feminine is the specified feature value, while masculine serves as the absence of gender specification, consistent with the classic analysis proposed by Harris 1991; see also Kramer 2015).…”
supporting
confidence: 83%
“…Finding sensitivity to both singular and plural agreement errors, we concluded that number in the native baseline is a multi-valued feature (both singular and plural are specified feature values; cf. Sauerland 2003;Scontras 2013a;. Finding sensitivity only to agreement errors involving feminine adjectives, we concluded that gender is single-valued (feminine is the specified feature value, while masculine serves as the absence of gender specification, consistent with the classic analysis proposed by Harris 1991; see also Kramer 2015).…”
supporting
confidence: 83%
“…Although we will not be committed to a particular view of the semantics of phi-features in this paper, it is worthwhile demonstrating this more concretely, adopting one particular analysis. Let us tentatively assume that pronominal phi-features are presupposition triggers (Heim 2008;Heim and Kratzer 1998;Sauerland 2003Sauerland , 2008aSchlenker 2003; but see Stokke 2010; Sudo 2013 for criticisms). For expository purposes, we assume that pronouns have internal structures as illustrated by (45) for 'her' with index i:…”
Section: (44)mentioning
confidence: 99%
“…Disregarding the issue of semantically vacuous phi-features (see Heim 2008;Percus 2006;Sauerland 2003Sauerland , 2008aSpector 2007), the features in (45) can be given the following meanings.…”
Section: (44)mentioning
confidence: 99%
See 2 more Smart Citations